Mechanical properties of bioceramic reinforced bone cement - (:unkn) unknown (My University, 2006)
There is currently a global effort to improve mechanical properties and biological performance of bone cements by reinforcing them with calcium phosphate ceramics. Silanation is used when reinforcing bone cements with ceramics. In this study, bovine hydroxyapatite (BHA), synthetic hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP) were treated with γ-methacryloxy propyl trimethoxy silane (A-174, 0.2%). The quantities of the silane-treated ceramic fillers in the cement were 1.5 wt%, 2.5% and 3.5%. Commercial CMW™3 bone cement was used as control group. The bone cement with 1.5% BHA showed the highest compressive strength (91.3 MPa). The bone cement with 1.5% HA showed maximum bending strength (137.9 MPa). The optimum amount of bioceramics additives seems to be in the range of 1.5% and 2.5%, since addition of higher amounts of bioceramics caused a decrease of mechanical properties of the produced bone cements. In the light of the demand for bioactivity for the produced bioceramics reinforced bone cements, the experimental results indicate the naturally derived BHA to reinforce the PMMA bone cements since the mechanical properties of the produced bone cements were similar to other calcium phosphate bioceramics.
Keywords: β-tricalcium phosphate (β-TCP); Bone cement; Bovine hydroxyapatite (BHA); Mechanical properties; Polymethylmethacrylate (PMMA); Silanation